Contributions of physical function and satisfaction with social roles to emotional distress in chronic pain: a Collaborative Health Outcomes Information Registry (CHOIR) study. Issue 12 (December 2015) - Sturgeon, John A.; Dixon, Eric A.; Darnall, Beth D.; Mackey, Sean C.
Abstract : Abstract: Individuals with chronic pain show greater vulnerability to depression or anger than those without chronic pain, and also show greater interpersonal difficulties and physical disability. The present study examined data from 675 individuals with chronic pain during their initial visits to a tertiary care pain clinic using assessments from Stanford University's Collaborative Health Outcomes Information Registry (CHOIR). Using a path modeling analysis, the mediating roles of Patient-Reported Outcomes Measurement Information Systems (PROMIS) Physical Function and PROMIS Satisfaction with Social Roles and Activities were tested between pain intensity and PROMIS Depression and Anger. Pain intensity significantly predicted both depression and anger, and both physical function and satisfaction with social roles mediated these relationships when modeled in separate 1-mediator models. Notably, however, when modeled together, ratings of satisfaction with social roles mediated the relationship between physical function and both anger and depression. Our results suggest that the process by which chronic pain disrupts emotional well-being involves both physical function and disrupted social functioning. However, the more salient factor in determining pain-related emotional distress seems to be disruption of social relationships, than global physical impairment. These results highlight the particular importance of social factors to pain-related distress, and highlight social functioning as an important target for clinical intervention in chronic pain. Abstract : Supplemental Digital Content is Available in the Text.Pain intensity affects anger and depression sequentially, distally through disrupted physical function and more proximally through disruptions in satisfaction with social roles and activities.